Schwannoma of the Floor of the Mouth - Rayamajhi, P; Parajuli, R (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.2 Issue 2 (July-Dec 2011) 21-22 DOI: http://dx.doi.org/10.3126/njenthns.v2i2.6800